Language Development in Children From The Perspective of The Philosophy of Science - Rahayu, Puji; Novikasari, Ifada (International Proceedings of Nusantara Raya, 2024)
Today's children often use digital technology, which allows them to access information quickly. However, there are concerns that excessive use of technology can reduce the social interactions that are essential for language development. This research examines language development in children from the perspective of the philosophy of science, with a focus on understanding how this process occurs in the context of scientific thinking. The surprising phenomenon that was raised was the fact that children's language development is often considered natural, even though it involves complex cognitive processes and is based on certain epistemological principles. This research was conducted in the educational environment of elementary school children. The aim is to analyze the relationship between the process of language development and philosophical approaches in the theory of knowledge. The method used is qualitative with a phenomenological approach, involving observation and in-depth interviews with educators and parents. The research results show that children's language development is not just a matter of stimulus-response, but is also influenced by their understanding of the world through social interaction and direct experience, which is in line with Lev Vygotsky's thinking